Acetyl-L-carnitine (ALCAR) to enhance nerve regeneration in carpal tunnel syndrome: study protocol for a randomized, placebo-controlled trial. Issue 1 (December 2016) - Curran, Matthew; Olson, Jaret; Morhart, Michael; Sample, Dory; Chan, K.
Abstract Background Carpal tunnel syndrome (CTS) is the most common form of peripheral nerve injury, affecting approximately 3 % of the population. While surgery is effective in mild and moderate cases, nerve and functional recovery are often not complete in severe cases. Therefore, there is a need for adjuvant methods to improve nerve regeneration in those cases. Acetyl-L-carnitine (ALCAR) is involved in lipid transport, vital for mitochondrial function. Although it has been shown to be effective in various forms of neuropathies, it has not been used in traumatic or compressive peripheral nerve injury. Methods In this pilot study we will utilize a double-blind, randomized, placebo-controlled design. Inclusion criteria will include adult patients with severe CTS. This will be confirmed by nerve conduction studies and motor unit number estimation (MUNE). Only those with severe motor unit loss in the thenar muscles (2 standard deviations [SD] below the mean for the age group) will be included. Eligible patients will be randomized to receive 3, 000 mg/day of ALCAR orally or placebo following carpal tunnel release surgery for 2 months. The primary outcome will be MUNE with supplementary secondary outcome measures that include: 1) two-point discrimination; 2) Semmes-Weinstein monofilaments for pressure sensitivity; 3) cold and pain threshold for small fiber function; 4) Boston self-assessment Carpal Tunnel Questionnaire and 5) Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire for symptom severity; and 6) Purdue Pegboard Test for hand functional performance. To follow post treatment recovery and monitor safety, patients will be seen at 3 months, 6 months and 1 year. The outcome measures will be analyzed using two-way ANOVA, with treatment assignment and time points being the independent factors. If significant associations are detected, a post hoc analysis will be completed. We aim to recruit ten patients into each of the two groups. Data from this pilot will provide the basis for power calculation for a full-scale trial. Discussion ALCAR is a physiologic peptide crucial for fatty acid transport. ALCAR has been shown to be effective in neuroprotection in the central nervous system and increase peripheral nerve regeneration. This has been applied clinically to various systemic peripheral neuropathies including diabetic neuropathy, antiretroviral toxic neuropathy, and chemotherapy-induced peripheral neuropathy. While animal evidence exists for the benefit of ALCAR in compression neuropathy, there have been no human studies to date. This trial will represent the first use of ALCAR in peripheral nerve injury/compression neuropathy. Trial registration NCT02141035 ; 20 April 2015